Improving performance of transcritical CO2 systems, using phase change materials (PCM) in a cold storage application - (:unkn) unknown (International Institute of Refrigeration, 2019)
Thermal energy storage is one of the most promising solutions for energy savings and increasing efficiency. To improve the performance of cold storage applications, incorporating phase change materials (PCM) to these systems, is a new approach. In this study, the performance of a transcritical CO2 refrigeration with a PCM incorporated supermarket refrigerator was investigated experimentally. The supermarket refrigerator was operated at evaporation temperature of-10 oC and cooling capacity of 4.2 kW. The PCM was chosen to have a melting and freezing point temperature of-4 oC. Differential Scanning Calorimeter (DSC) device was used to determine properties of salt solutions such as melting/freezing temperatures and latent heat of fusion and freezing. In order to determine the system performance, compressor on-off time and its duration were measured for the cases with and without PCMs. It is revealed that by addition of PCMs, the compressors runtime was decreased meaningfully. © 2019 IIF/IIR.
Keywords: Cold Storage; COP; Phase Change Material; Trancritical CO2 Systems